2018
DOI: 10.1111/hsc.12644
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a community based dental clinic for youth experiencing homelessness in Brisbane

Abstract: The relationship between homelessness and ill health is complex, and many risk factors for homelessness such as unemployment, low income, and substance abuse are also risk factors for poor oral health. In order to overcome barriers to access dental care, previous studies have recommended integrating dental care, referral pathways, and information within the overall care provided by support services available to people at risk of homelessness. This study aimed to evaluate a dental service developed and implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
(31 reference statements)
0
6
1
Order By: Relevance
“…We found that 42 out of 89 (47%) of patients had completed a treatment plan, while 27% failed to return for treatment completion. In contrast, previous research evaluating services for people experiencing homelessness 7,9,16,21 demonstrated lower levels of attendance and completion. A review of 204 patients attending a targeted dental service in London from 1992 to 2001, indicated that only 18% completed their treatment 7 .…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…We found that 42 out of 89 (47%) of patients had completed a treatment plan, while 27% failed to return for treatment completion. In contrast, previous research evaluating services for people experiencing homelessness 7,9,16,21 demonstrated lower levels of attendance and completion. A review of 204 patients attending a targeted dental service in London from 1992 to 2001, indicated that only 18% completed their treatment 7 .…”
Section: Discussioncontrasting
confidence: 72%
“…A review of 204 patients attending a targeted dental service in London from 1992 to 2001, indicated that only 18% completed their treatment 7 . A community clinic in Australia providing dental care to young people experiencing homelessness had a high percentage of failure‐to‐attend (57%) pre‐booked appointments 21 . A unique feature of the care pathway developed by PDSE, and found to be crucial for the success of the clinic, is the role of a link worker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] To improve uptake and utilization by disadvantaged groups, past research recommends that dental services become more targeted, community-centred and integrated into broader primary models of care such as homeless health care programs. 2,16,[20][21][22] Communitycentred dental clinic (CDC) care is one approach attempting to provide more targeted and accessible care to disadvantaged groups. 10,13,22 CDCs generally rely on a combination of government support and community donations, operating as not-for-profit clinics integrated within broader community health centres or as mobile services delivering outreach programs.…”
Section: The Official Journal Of the Australian Dental Associationmentioning
confidence: 99%
“…25 They are a likely reflection of higher rates of untreated oral disease and lower access to dental care commonly experienced by disadvantaged groups. [2][3][4][5][6]14,20,25 A similar study by Daly et al 5 proposed that greater sensitivities to oral health impacts by the homeless are due to its heightened importance in the experience of disadvantage. The importance of dental appearance for selfconfidence, social functioning and levels of esteem in the experience of disadvantage is reported in the literature.…”
Section: Oral Health Impacts Upon Quality Of Lifementioning
confidence: 99%